Public Key Cryptosystem Based on Polynomial Composition - Maxrizal Maxrizal; Baiq Desy Aniska Prayanti (Indonesian Journal of Mathematics Education, 2019)
The public key cryptosystem is an extension of an asymmetric key cryptosystem. The public key cryptosystems have been developed based on the concepts of matrix, polynomial and polynomial decomposition. In this study, we will introduce the public key cryptosystem over polynomial composition. This research is a literature study. The results show that the polynomial composition can be used in public-key cryptosystems by modifying special functions to apply commutative properties.